2016
DOI: 10.1007/s00441-016-2402-1
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan scaffolds induce human dental pulp stem cells to neural differentiation: potential roles for spinal cord injury therapy

Abstract: Cell-based transplantation strategies hold great potential for spinal cord injury (SCI) repair. Chitosan scaffolds have therapeutic benefits for spinal cord regeneration. Human dental pulp stem cells (DPSCs) are abundant available stem cells with low immunological incompatibility and can be considered for cell replacement therapy. The purpose of this study is to investigate the role of chitosan scaffolds in the neural differentiation of DPSCs in vitro and to assess the supportive effects of chitosan scaffolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 34 publications
0
78
0
2
Order By: Relevance
“…Transplantation of NS/PCs is promising treatment for SCI. [99][100][101][102][103] NS/PCs usual has been studied as a mean to replace the damaged neurons in SCI. However, increasing data showed that NSCs can promote motor functional recovery by modulating the host environment.…”
Section: Ns/pcs and Macrophage Polarizationmentioning
confidence: 99%
“…Transplantation of NS/PCs is promising treatment for SCI. [99][100][101][102][103] NS/PCs usual has been studied as a mean to replace the damaged neurons in SCI. However, increasing data showed that NSCs can promote motor functional recovery by modulating the host environment.…”
Section: Ns/pcs and Macrophage Polarizationmentioning
confidence: 99%
“…On the other hand, allografts, xenografts, or artificial bone substitutes may expose the patient to severe risks of foreign body reactions and infections (5). Stem cells represent the new frontier in the field of regenerative medicine and are seen as a promising and suitable means to overcome the aforementioned drawbacks (6)(7)(8). Numerous studies report that adult stem cells can be isolated from several organs and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…SC populations in dental and central niches are potentially important in contributing to revitalization procedures including dental pulp stem cells (DPSCs), stem cells for the apical papilla (SCAPs), human periodontal ligament stem cells (PDLSCs) as well as centrally residing SC populations such as human bone marrow stromal stem cells (BMSSCs), and hematopoietic stem cells (HSCs) [47]. SC behavior can be modulated by producing GFs themselves [29] and by GFs released from dentin [48], other cells [49], or scaffold materials [31]. …”
Section: Reviewmentioning
confidence: 99%